Sulphide oxidation, oxygen diffusion and metal mobility in sulphide-bearing mine tailings in Northern Sweden - Alakangas, Lena (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2006)
Large quantities of sulphide-bearing mining wastes produced from ore processing are deposited throughout the world. Sulphide oxidation in the wastes may release acidic water with high concentrations of metals to the environment. Remediation strategies are usually site specific, since the physical and chemical properties of the wastes vary. Therefore, sulphide oxidation, oxygen diffusion and metal mobility in unoxidised and oxidised, remediated and unremediated wastes have been studied in the present work. The efficiency of different cover systems on unoxidised tailings from Kristineberg, were studied in pilot-scale test cells (5*5*3 m3)under field conditions. Clayey till, sewage sludge, apatite and Trisoplast were used as sealing layers and unspecified till as a protective cover. In one cell tailings were left uncovered. Unoxidised tailings in the test-cells in the initial stage after deposition showed relatively low sulphur release (600- 800 mg/l)in leachate waters, which probably was an effect of high moisture content in the tailings prior to deposition. Near-neutral pH found in the leachates was an effect of neutralisation by carbonate minerals present and lime (Ca(OH)2) added prior to deposition. Similar sulphur concentrations were found also in the uncovered tailings. The sulphide oxidation rate increased with time in the uncovered tailings, and decreased in the covered. The lowest oxygen concentrations were observed below the cover system with sewage sludge, which was the most effective barriar against oxygen in a short-term perspective. The oxygen fluxes through the clayey till and apatite layers were within the same magnitude and varied between 0.5 and 4 mole/year,m2. The Trisoplast layer seemed to have failed as a barrier against oxygen. Tailings studied at field scale at Laver and Kristineberg had oxidised for more than 50 years. The tailings at Kristineberg have high pyrite content (c.25% and 50%) and those at Laver have low grade of pyrrhotite (2-3%). The Laver tailings are unremediated, while at ...